(untitled) (International Journal of Physiotherapy, 2016)
Background: Prevalence of flatfoot is highly variable in different world populations. Previous studies have found that many factors are associated with flatfoot. The objective of the present study was to investigate the prevalence of flatfoot and its association with age, gender and BMI in group of 6-10 aged children in Central province of Sri Lanka. Methods: A total of 722 children aged 6 to 10 were used to assess normalize navicular height using two clinical measurements (navicular height, truncated foot length). Weight and height of the subjects were measured to calculate body mass index. Age and gender of the children were also recorded. Calculated normalize navicular heights were plotted in a distribution curve and area under the curve between +1SD and -1SD was considered as normal foot. Area under the curve which is left to the -1SD was considered as flatfoot. Results: Overall prevalence of flatfoot among 6-10 aged children in the present sample was 16.06%. The prevalence of flatfoot in 6,7,8,9 and 10 aged children were 26.35%, 16.19%, 12.75%, 13.57% and 11.1%, respectively. Prevalence of flatfoot was high in overweight children (21.05%). Prevalence of flatfoot among males and females were 47% and 53%,respectively. Conclusion: This study suggests that there is a significant association between flatfoot and age (p<0.05). Prevalence of flat foot decreases with advancing age. Furthermore, there is a significant association between flatfoot and body mass index (p<0.05). Prevalence of flatfoot is higher in overweight children than normal weight and underweight children. There is no significant association between flatfoot and gender.